ANALISIS PEMENUHAN HAK-HAK WARGA BINAAN DITENGAH TERJADINYA OVERCAPACITY LEMBAGA PERMASYARAKATAN DI INDONESIA - Firmansyah Fijri (2023)
Overcapacity is a condition where the number of prison inmates exceeds the available capacity. This can occur due to several factors such as the growth in the number of occupants that is not balanced with the available occupancy capacity. This overcapacity has negative implications in view of several things in prisons, namely causing prison performance in running the correctional system to be less than optimal so that the fulfillment of the basic rights of inmates is disrupted. In this study the authors used normative juridical methods and statutory approaches (statute approach). The aim of the research is to find out the protection and guarantee of the fulfillment of the rights of inmates in prisons and the efforts to overcome them. The inmates here consist of three main components namely convicts, inmates, and correctional clients. The rights of the assisted citizens themselves are regulated in Article 9 to Article 15 of Law Number 22 of 2022 Concerning Corrections. As a result, the authors found that even though the state has guaranteed the rights of convicts as human rights through legal regulations, in practice these rights have not been implemented optimally due to limitations in their implementation in correctional institutions. Efforts have been made to deal with the impact of overcapacity on inmates, namely reducing the number of inmates by providing social reintegration, such as granting assimilation, parole, parole leave, leave before release, and transfer of inmates to other prisons. In addition, non-institutional criminal efforts are also implemented, namely by providing conditional punishment, restitution, or restorative justice. The government is expected to be able to regulate the correctional system properly and balance the number of inmates so that supervision is implemented more effectively.